THE IDENTIFICATION OF PSEUDOMONAS AERUGINOSA IN DIVERSE CLINICAL SPECIMENS AND THE PATTERN OF ANTIBIOTIC RESISTANCE IN HUMANS - Muhanna Redha, Huda; Jawad Hussein, Basim; Sadiq Alqaisi, Ali Abbas; Kadhim Hamadan, Wisam; Hadi Obiad, Zahraa; Jalal Abood, Ali (Journal of Medical Genetics and Clinical Biology, 2025)
Objective: This study aims to identify the pollution foci of Pseudomonas aeruginosa (P. aeruginosa) in hospital environments, utilizing a random sampling approach to collect diagnostic data from various sources in Al-Karama Teaching Hospital and Al-Hey Hospital. Methods: Eighty samples were collected, evenly distributed with 40 samples from each hospital. Biochemical and agronomic tests were conducted to identify P. aeruginosa isolates. Antibiotic sensitivity was assessed for ten isolates using the Kirby-Bauer disc diffusion method across ten antibiotic classes. Results: The tests identified ten isolates of P. aeruginosa. The antibiotic sensitivity evaluation revealed that nearly all isolates exhibited considerable resistance to the antibiotics tested, demonstrating a broad spectrum of resistance to multiple antibiotic classes. Novelty: This study highlights the prevalence of P. aeruginosa in hospital settings and its significant resistance to commonly used antibiotics, emphasizing the critical need for enhanced infection control measures and antibiotic stewardship in healthcare facilities.